P611 Incidence, clinical presentation, and severity of SARS-CoV-2 infection in IBD patients in the second and the third wave of infection. (27th May 2021) - Algaba Garcia, A; Guerra, I; Castro, S; Jiménez, L; Garza, D; Aller, M D M; Granja, A; Guardiola, A; Bellart, M; Pizarro, N; Bermejo, F
Abstract: Background: Data about the SARS-CoV-2 infection in inflammatory bowel disease patients (IBD) are scarce. Our aim was to analyse the incidence, clinical presentation, and severity of SARS-CoV-2 infection in IBD patients in the second and the third wave of infection. Methods: Cross-sectional, observational study in IBD patients with confirmed SARS-CoV-2 infection by RCP and/or antigen tests from 01 July 2020 to 01 March 2021. All data were collected by telephone interview and reviewing the electronical medical records. Results: Fifty-one of 805 IBD patients followed in our Unit were diagnosed of SARS-CoV-2 infection in this period (6.3%; 95% CI 4.6–8.0). Mean age: 45±13 years old; 56.9% female, 23.5% smokers, 56.9% Crohn's disease, 29.4% comorbidities and 17.6% asymptomatic. Digestive symptoms were reported in 22 patients (43.1%), with diarrhoea as the most common (39.2%, median duration: 4 days; IQR 1–7). The most frequent symptoms other than diarrhoea were low-grade fever/fever in 43.1% (median duration: 3 days; IQR 1–6.5) and dysosmia/dysgeusia in 39.2% (median duration: 15 days; IQR 7–30). Only one patient (2%) was diagnosed with IBD flare-up during infection. Six patients (11.8%) temporarily withdrew their IBD treatment because of COVID-19. Most of the patients had a mild disease (88.2%), no patient had to be admitted in the intensive care unit. Only one patient died (2%) due to SARS-CoV-2 infection and multiple previous comorbidities, 52 years old male with ulcerative colitis in treatment with Mesalazine and dendritic cell sarcoma, common variable inmunodefiency, and primary sclerosing cholangitis progressing to cirrhosis. In the multivariate analysis, the presence of dyspnoea was associated with more severe infection (p=0.007; OR:25.7; 95% CI 2.4–277.8). Patients on immunomodulators and/or biological therapy did not have more severe disease compared to non-immunosuppressed patients (p>0.05). Conclusion: SARS-CoV-2 infection was relatively frequent is our series. Dyspnoea was associated with a more severe infection. Severity of SARS-CoV-2 infection was not related to immunosuppression or development of IBD flare-ups and only a small percentage of patients needed to modify IBD medication during infection